THE EFFECTIVENESS OF MIND MAPPING IN TEACHING DESCRIPTIVE-TEXT WRITING TO THE FIRST GRADE STUDENTS OF “DHARMA KARYA UNIVERSITAS TERBUKA” JUNIOR HIGH SCHOOL, PONDOK CABE ILIR - Nerisha Arviana; Muhammad Ahsan Tampubolon (Universitas Pamulang, 2022)
The objective of this research is to find empirical evidence of whether or not mind mapping technique is effective in teaching descriptive-text writing to the first-grade students of “Dharma Karya Universitas Terbuka” Senior High School, Pondok Cabe Ilir. The method of the research was a pre-experiment. The writer conducted pre-test to the students’ writing skill to make descriptive text at the first. Then the writer taught writing descriptive text in experiment class by using mind mapping. In the last meeting the writer gave a post-test to know the effect of the increase of the students’ writing skill in making descriptive texts. The data that the writer collected is quantitative in the forms of scores representing how skillful the students in writing descriptive text. In collecting the data of this research, the writer used a pre test and a post test. In the first meeting, the writer gave a pre-test to know the level of the students’ competence at the beginning in writing descriptive texts. In the last meeting, the writer gave a post-test to know the increase of students’ writing skill after they followed the teaching-learning process using mind mapping.